An Absolutely Patient Action: The Translator as a Figure of Ethical Communication - Margaret Schwartz ([sic])
What does the translator do? Does she transcribe, performing an almost technical function? Or is she an inventor, an interpreter, a kind of singer of lost songs? This is the question Benjamin posed as the translator’s task (Benjamin); here I explore the possibility that translation is liturgy. Translation as either a technical transcription or interpretive intervention neglects its core concern: ethics. Translation is dialogic, speaking from one language to another, yes, but also from a space between languages. The translator voices, though she does not author. The translator’s orientation is always towards respect for another voice – that of the source text. And the translator’s task is always impossible, insofar as total respect (ciphered as total fidelity) gives way to what is inevitably “lost in translation.” Whatever the translator does, she is oriented always towards managing this loss, towards the ethical stakes of this loss. Seen in this light, whether she transcribes or invents becomes a very different question.